School inspectors and educational change - Mancebo, María Ester; Romero, Margarita (Universidad Centro Latinoamericano de Economía Humana (Universidad CLAEH), 2021)
School supervisors constitute a fundamental link in any process of educational transformation. This article aims to understand its role in the multiple innovations implemented in Uruguay during the «progressive era» (2005-2020) in which the national government was led by a center-left party, the Frente Amplio. The article was nourished by bibliography on teachers´ supervision and on change processes, with contributions from both Pedagogy and Political Science. The research carried on was descriptive and explanatory, qualitative in nature and with a comparative tone. As main findings, the document emphasizes that, under the same institutional framework, the position of Primary supervisors towards innovations diverged from that assumed by supervisors in the Secondary level. At an explanatory level, it was found that the role of supervision in educational transformation derives not only from the dominant institutional framework but also from political support, the modality of implementation of innovative policies, the prevailing professional culture and the weight of history.